Evaluation of deoiled corn dried distillers grains with solubles (solvent extracted) on growth performance of nursery pigs - J Y Jacela; L Brandts; R C Thaler; D Peters; D E Little; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 210 pigs (initially 22.0 lb) were used in a 28-d study to evaluate the effects of increasing deoiled corn dried distillers grains with solubles, solvent extracted (dDGS) on nursery pig growth performance. Pigs were blocked on the basis of pen weight and randomly allotted to 1 of 5 dietary treatments containing 0, 5, 10, 20, or 30% dDGS. There were 7 pens per treatment and 6 pigs per pen. All diets were formulated to equivalent ME and standardized ileal digestible lysine concentrations. Soybean oil was added to the dDGS diets as an energy source to equalize dietary ME of the 5 treatments. Pigs from each pen were weighed as a group and feed consumption was obtained on d 0, 14, and 28 to determine ADG, ADFI, and F/G. Overall, feeding diets with increasing dDGS had no effect (P>0.46) on nursery pig ADG, ADFI, and F/G. In conclusion, dDGS can be included at levels up to 30% in nursery pig diets for pigs weighing between 22 to 50 lb without affecting growth performance provided fat is added to the diet to offset the low energy content of dDGS.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Deoiled corn; Feed ingredient; Growth; Nursery pig